2022
DOI: 10.1007/s10639-022-11298-9
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly discourse of the fourth industrial revolution (4IR) and education in Botswana: a scoping review

Abstract: Implementation of the practices of the Fourth Industrial Revolution (4IR) is currently a trendy topic worldwide since various interruptions are expected. Education is considered as a major tool to equip people with the necessary kills to be prepared for the Fourth Industrial Revolution (4IR). Botswana’s education system was ranked among the top ten on the African continent. Hence, this study explored the 4IR and education in Botswana, using a scoping review. The literature was analysed and presented, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In other words, schools were compelled to rethink literacy pedagogy in the context of the 4IR and expose their learners to internet-based online platforms. For example, Uleanya (2023) carried out a study in Botswana with a particular emphasis on the academic discourse of the 4IR and schooling. The study's findings revealed that challenges including curriculum problems and a shortage of electricity http://www.rw.org.za Open Access in remote regions, among other things, were getting in the way of Botswana's efforts to continue preparing for the 4IR through education.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, schools were compelled to rethink literacy pedagogy in the context of the 4IR and expose their learners to internet-based online platforms. For example, Uleanya (2023) carried out a study in Botswana with a particular emphasis on the academic discourse of the 4IR and schooling. The study's findings revealed that challenges including curriculum problems and a shortage of electricity http://www.rw.org.za Open Access in remote regions, among other things, were getting in the way of Botswana's efforts to continue preparing for the 4IR through education.…”
Section: Introductionmentioning
confidence: 99%
“…The findings in this section indicate that there is a challenge with human capital in Botswana. In support of this, a study by Uleanya (2022) averred that the achievement of the 4IR practices is founded on the availability of human capital. However, in Botswana, there are several challenges, such as a shortage of qualified personnel, a lack of funds, limited equipment, and non-alignment of the curricula of schools with the demand for the 4IR (Uleanya, 2022).…”
Section: Human Capitalmentioning
confidence: 99%
“…In support of this, a study by Uleanya (2022) averred that the achievement of the 4IR practices is founded on the availability of human capital. However, in Botswana, there are several challenges, such as a shortage of qualified personnel, a lack of funds, limited equipment, and non-alignment of the curricula of schools with the demand for the 4IR (Uleanya, 2022). A low level of computer literacy was also attested to by Raesima (2021), and this is affecting the uptake and usage of government esystems.…”
Section: Human Capitalmentioning
confidence: 99%